Research on Zero Carbon Design Method for Medical Buildings in Solar Enriched Areas – The Tibet Hospital of the West China Second University Hospital of Sichuan University - Mei Dou; Yuanping Zhang; Liu Yang; Huizhi Zhong; Chenyou Luo; Yan Liu (Chemical Engineering Transactions)
The achievement of the green and low-carbon objectives of medical buildings in solar-enriched areas not only relates to the local people's aspirations in terms of enhanced medical environment but also reflects the regional endeavors toward zero-carbonization of the construction field in the west of China. In view of the scarcity of conventional energy in the regions and the high energy consumption of medical buildings, the overarching path of "Overall objectives and adjustment, segmentation strategy and optimization" is employed. A study on zero-carbon design methodology is conducted with respect to the multi-factor coupling of "Spatial Priority - Synergistic Optimization of Renewable Energy and Construction." The validation of the design methodology is carried out using the project of Tibet Hospital of West China Second Hospital of Sichuan University as an example. Based on the segmented optimization and co-optimization methods under the whole life cycle perspective, the optimal solution proposed in this study can achieve a 14.4 % reduction in energy consumption, a 10.5 % reduction in carbon emission, and a 4.6 % increase in the useful daylight illuminance. Solar enriched area, Medical buildings, Zero carbon building, Architecture design, Technology